EFFECT OF SHADE AND SOWING METHOD ON ERYNGIUM FOETIDUM PRODUCTION - Mozumder, Shailendra Nath; Haque, M. I.; Zaman, M. M.; Shahiduzzaman, M. (International Journal of Research -GRANTHAALAYAH, 2021)
The experiment was conducted at two Regional Spices Research Stations at Gazipur and Magura during July 2012 to June 2014. Experiments were conducted following split plot design with six treatment of two factors of three different shades such as 1) Black mosquito net, 2) Cucurbit trellis and 3) Control (open) and two sowing methods such as i) line sowing with 10cm spacing and ii) Broadcasting were placed in the unit plot. The maximum number of harvested plants (655/m2) and fresh yield (28.52 t/ha) were obtained from broadcast sowing under nylon net shade at Joydebpur while line sowing without shade gave the minimum number of harvested plants (293/m2) and fresh plant yield (16.20 t/ha) at Magura. The maximum gross return (Tk. 4944.2 thousand/ha), net return (TK. 4438.2 thousand/ha) and BCR (1099) was obtained from nylon net shade in broadcast sowing and these was lowest (Tk. 1586.4, 1196.3 thousands/ha and 4.07, respectively) came from line sowing under cucurbits trellis. Cultivation of Eryngium under cucurbits trellis gave early returns that better for fresh leaf production. Open sunlight is less costly but it is not suitable for quality leaf production. Broadcasting sowing under nylon net shade seems better for leaf production and profit.